Islamic Religious Education Learning Strategies to Build Inclusive Religious Character for University Students - Sutarto Sutarto; Dewi Purnama Sari (STAI Hubbulwathan Duri, 2022)
This phenomenological qualitative research aims to explore the learning strategies used by Islamic Religious Education lecturers in building the character of religious inclusion in the aspects of knowledge, feelings, and aspects of doing. The research informants comprised 15 lecturers who teach religious subjects at the Islamic Religious Education Study Program IAIN Curup. Data was collected using semi-structured interviews. The data collected was analyzed in three steps: data collection, data reduction, data presentation, conclusion drawing and verification. The validity of the data was checked using triangulation of technical sources. The results show that learning strategies to build character in religious intelligence can be carried out not only by providing knowledge and understanding. However, it must be accompanied by the development of attitudes, feelings, skills, and training to cooperate and provide students with real-life experience in a plural society.